Effect of octene content on peroxide crosslinking of ethylene–octene copolymers. Issue 2 (21st June 2012) - Svoboda, Petr; Poongavalappil, Sameepa; Theravalappil, Rajesh; Svobodova, Dagmar; Mokrejs, Pavel
Abstract Various ethylene–octene copolymers were crosslinked by dicumyl peroxide. Octene content was 16, 20, 30, 35 and 38 wt% and melt flow index was 1 or 3 g/10 min. The concentration of dicumyl peroxide was 0.3, 0.5 and 0.7 wt%. Crosslinking was analyzed by a rubber process analyzer in the temperature range 150–200 °C. Cross‐linkability was evaluated from the real part modulus s'maxversus peroxide level plots as the slope of the line. With decreasing octene content and increasing melt flow index the crosslinkability increased. This was confirmed also by tan δ analysis. The network density was measured by the gel content. A higher gel content was found for melt flow index 3 and low octene content. The melting points Tm and the crystallinities were evaluated by DSC. © 2012 Society of Chemical Industry